Synergistic Manipulation of Zn2+ Ion Flux and Nucleation Induction Effect Enabled by 3D Hollow SiO2/TiO2/Carbon Fiber for Long‐Lifespan and Dendrite‐Free Zn–Metal Composite Anodes. (13th September 2021) - Xue, Pan; Guo, Can; Wang, Nanyang; Zhu, Kaiping; Jing, Shuang; Kong, Shuo; Zhang, Xiaojie; Li, Li; Li, Hongpeng; Feng, Yongbao; Gong, Wenbin; Li, Qiulong
Abstract: Aqueous rechargeable zinc–metal batteries are a promising candidate for next‐generation energy storage devices due to their intrinsic high capacity, low cost, and high safety. However, uncontrollable dendrite formation is a serious problem, resulting in limited lifespan and poor coulombic efficiency of zinc–metal anodes. To address these issues, a 3D porous hollow fiber scaffold with well‐dispersed TiO2, SiO2, and carbon is used as superzincophilic host materials for zinc anodes. The amorphous TiO2 and SiO2 allow for controllable nucleation and deposition of metal Zn inside the porous hollow fiber even at ultrahigh current densities. Furthermore, the as‐fabricated interconnected conductive hollow SiO2 and TiO2 fiber (HSTF) possess high porosity, high conductivity, and fast ion transport. Meanwhile, the HSTF exhibits remarkable mechanical strength to sustain massive Zn loading during repeated cycles of plating/stripping. The HSTF with interconnected conductive network can build a uniform electric field, redistributing the Zn 2+ ion flux and resulting in smooth and stable Zn deposition. As a result, in symmetrical cells, the Zn@HSTF electrode delivers a long cycle life of over 2000 cycles at 20 mA cm −2 with low overpotential (≈160 mV). The excellent cycling lifespan and low polarization are also realized in Zn@HSTF//MnO2 full cells. Abstract : An effective strategy to construct a 3D porous hollow fiber scaffold with well‐dispersed TiO2, SiO2, and carbon as the superzincophilic host materials for zinc anodes is reported. The hollow fiber redistributes the Zn 2+ ion flux, resulting in stable Zn deposition, which allows the composite electrode to demonstrate a long cycle life of over 1500 cycles at 20 mA cm −2 .